Climate change effects on plant-soil feedbacks and consequences for biodiversity and functioning of terrestrial ecosystems - Pugnaire, Francisco I. (2020)
Plant-soil feedbacks (PSFs) are interactions among plants, soil organisms, and abiotic soil conditions that influence plant performance, plant species diversity, and community structure, ultimately driving ecosystem processes. We review how climate change will alter PSFs and their potential consequences for ecosystem functioning. Climate change influences PSFs through the performance of interacting species and altered community composition resulting from changes in species distributions. Climate change thus affects plant inputs into the soil subsystem via litter and rhizodeposits and alters the composition of the living plant roots with which mutualistic symbionts, decomposers, and their natural enemies interact. Many of these plant-soil interactions are species-specific and are greatly affected by temperature, moisture, and other climate-related factors. We make a number of predictions concerning climate change effects on PSFs and consequences for vegetation-soil-climate feedbacks while acknowledging that they may be context-dependent, spatially heterogeneous, and temporally variable.